An exploration of the performance behaviors of lubricated textured and conventional spur gearsets. (December 2018) - Gupta, Niharika; Tandon, N.; Pandey, R.K.
Abstract: This paper reports the experimental investigations on the performance behaviors of the conventional and textured gearsets. The vibration behaviors, temperature rise and surface topography of gearsets have been investigated for different loads ( P H ) and pitch line velocities. The texture comprising of micro-cylindrical dimples of non-uniform diameter was created by chemical etching process on teeth surface. The vibration results obtained employing conventional and textured gearsets have been compared and analysed in time and frequency domains. Moreover, the surface topography and temperature rise have been measured. Based on the experimental results, it is found that in the presence of texture on gear teeth, the vibration amplitudes, oil film temperature rise and teeth surface damage have substantially reduced. Highlights: Experimental evaluation of performance behaviors of the textured gearset has been carried out. Comparisons of performance behaviors of conventional and textured gearset have been reported. Vibration spectra of the conventional and textured gearsets have been investigated in time and frequency domains. Surface topography of conventional and textured teeth faces have been studied using SEM and 3D-profilometer. Moreover, temperature rise in both the cases has been recorded using infrared camera (thermography). Significant reductions in the vibration amplitudes and oil film temperature rise have been observed with textured gear. The surface damage of textured teeth has reduced significantly compared to the conventional gear surface.